Challenges in Teaching English to Young Learners - Dita Rizki Anggraini (Jurnal Bahasa dan Sastra, 2018)
Abstract: The consideration of English to be introduced at the earlier age has been arisen, especially in Indonesia. EF EPI in 2018 shows that Indonesia is in the 51st place out of 88 countries which indicates as having a low English proficiency. Likewise, in Asia, Indonesia is placed in the 13th place out of 21 countries which also categorizes Indonesia of having a low proficiency. Thus, it is crucial to teach English as early as possible. However, teachers of EYL all over the world, including Indonesia are facing some challenges in carrying out their profession. In Indonesia, specifically, the challenges or problems come from the status of English in Indonesia, teachers’ pedagogical competency, and parents’ socio-economic background. Keywords: challenges, English for young learners, teaching English to young learners Abstrak: Pertimbangan akan pentingnya pengenalan bahasa Inggris sejak dini kini semakin meningkat, khususnya di Indonesia. EF EPI pada tahun 2018 menempatkan Indonesia pada posisi ke-51 dari 88 negara yang mengindikasikan rendahnya kemampuan siswa dalam berbahasa Inggris. Bahkan di tingkat Asia, Indonesia juga termasuk salah satu negara dengan kemampuan bahasa Inggris yang rendah (peringkat 13 dari 21 negara). Oleh karenanya, mengajarkan bahasa Inggris sedini mungkin menjadi suatu hal yang krusial. Akan tetapi, guru-guru bahasa Inggris di sekolah dasar maupun sekolah menengah pertama di seluruh dunia, termasuk Indonesia, kerap menghadapi tantangan-tantangan dalam menjalankan profesi mereka. Terkhusus di Indonesia, tantangan-tantangan atau masalah-masalah tersebut berasal dari status (mata pelajaran) bahasa Inggris di Indonesia, kompetensi pedagogik guru, dan latar belakang sosio-ekonomi para orang tua.Kata-kata kunci: tantangan, Bahasa Inggris untuk pembelajar muda, pengajaran Bahasa Inggris pada pembelajar muda